Analgesic Drug Use for Carpal Tunnel Syndrome - Tamara Audrey Kadarusman; Hanik Badriyah Hidayati; Paulus Sugianto (Faculty of Medicine Universitas Airlangga, 2019)
Introduction: Carpal tunnel syndrome (CTS) is a group of neuropathic symptoms regarding to the compression of median nerve which passing through carpal tunnel. There has been a great number of prevalence of CTS in Indonesia, which leads to decreasing quality of life, lack of work productivity, and increasing health cost. Analgesic treatments have been drug of choice for carpal tunnel syndrome for years. However, the effectiveness of the drug and the risk of adverse effect of drugs have always been an issue for analgesic use. An observational study on profile of analgesic drugs administration for carpal tunnel syndrome patients in Dr. Soetomo General Hospital SurabayaMethod: A descriptive observational retrospective study has been conducted to observe the profile of analgesic drugs administration, including type and dosage of drugs, classification of drugs, drugs administration route, early and advanced type of analgesics, and duration of analgesic administration. Sociodemographic data and clinical characteristics (main symptoms) of carpal tunnel syndrome patients are also included in this study.Results: Out of 202 subjects of this study, most patients are women (84,16%), the group age of 50-59 to years old, and the most frequent job is household wife (43,56%). The most common analgesic drugs used for carpal tunnel syndrome patients is 50 mg sodium diclofenac for 78 patients (38.61%). All of those subjects are administered with oral analgesic (100%). 185 patients (91.59%) are administered with analgesic combinations. The duration of analgesic usage are 7 days as an early analgesic in 82 patients (40.59%).Conclusion: CTS is a syndrome due to median nerve compression of the hand, Women, household wife, and age of 50-59 years old are found to be vulnerable to this syndrome. Analgesic drugs mostly used is 50 mg natrium diclofenac, orally, combined, with the period of 7 days for early medication